THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND EVALUATION MANAGEMENT ON ORGANIZATIONAL COMMITMENT IN SOCIETY - Ida Kusumawati; Akmal Mundiri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study aims to explore transformational leadership and evaluation management on organizational commitment in the community environment. Transformational leadership refers to efforts to create positive change in organizations that lead to motivation, inspiration, and create an environment that supports innovation by fostering a spirit of change. In addition, evaluation management also plays a crucial role in creating productive human resources for work effectiveness, assessing work results, and increasing the sense of responsibility among organizational members collectively. This study uses a descriptive approach, combining article analysis, relevant literature, and a survey of a number of organizational members in the community. The results of this study illustrate that transformational leadership has a positive impact and inspires leaders towards organizational member commitment. On the other hand, the systematic application of evaluation management is able to identify successes and improvements, as well as strengthen the sense of responsibility for tasks that are the goals of the organization. Thus, the combination of transformational leadership and evaluation management becomes an important reference and strategic goal to consciously strengthen organizational commitment, maintain the quality of service to the community, and improve the ability to adapt to various changes better.